Effective Use of Props in Promoting Oral Health among Kindergarten School Children in Makassar, South Sulawesi - Prastyo, Eko; Suharto, Suharto; Zaenal, Zaenal; Khasanah, Uswatun; Delimayani, Delimayani; Arda, Darmi; Nurhaedah, Nurhaedah (International Journal of Health Sciences, 2024)
Efforts to maintain oral health and develop dental health, especially among school children, need special attention because at this age children are undergoing a process of growth and development. The problem in this research is the high percentage of caries rates in kindergarten children in Makassar. This research aims to determine parents' knowledge about maintenance of oral health in kindergarten children in Makassar covers knowledge about understanding caries tooth, knowledge about reason caries teeth, knowledge about the consequences of dental caries, knowledge about preventing dental caries, and knowledge about dental caries treatment. This type of research is research descriptive with amount respondents 41 respondents. Method collection data with filling out the questionnaire. The data analysis technique used is recapitulation The results of the data that have been collected are then calculated for each parent's data students, then the results of the calculations presented in tabular form and then presented. The research results show parents' knowledge about health tooth and mouth including in category good.